Jalan Hidup Filosofis Muá¸¥ammad Ibn ZakariyyÄ Al-RÄzÄ« dan Relevansinya dengan Problem Psikologis Manusia Modern: Muá¸¥ammad Ibn ZakariyyÄâ€™ Al-RÄzÄ«â€™s Philosophical Life and Its Relevance to Modern Human Psychological Problems - Muh. Bahrul Afif (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2023)
Abstract Materialistic life orientation in the modern era is the reason for the emergence of various life problems, especially psychological problems. One of the psychological problems that arise is the meaninglessness of life or an existential vacuum. If it does not receive serious attention, then the problem has the potential to cause mental health disorders that, in fact, now plague many modern humans. Those who are sober, gradually begin to seek to find solutions to overcome the psychological burden by turning to certain life paths. Among them are those who dive into the world of spirituality, some go through philosophical paths such as Stoicism, which is now widely loved. Therefore, digging into various traditions to find the right solution in overcoming mental health disorders is paramount. Such efforts can also be made through Islamic philosophy. One philosopher who paid special attention to mental health issues was al-RÄzÄ«. This is contained in his thoughts on Philosophic Life. This is the main discussion in this study. The results of this study illustrate that although such thinking appears to defend misunderstood Socratesâ€™ life paths, yet the real philosophic lifeâ€”instead of imitating Socratesâ€”is to imitate the attributes of God. As for al-RÄzÄ«â€™s application of the Philosophic Life: training the control of passions; not hurting other beings; not hurting ourself; does not go beyond the extreme limits (defect or excess); and imitate the attributes of God to the extent of manâ€™s abilities. Keyword: Al-RÄzÄ«, Mental Health, Philosophic Life